Visualizing Personal Branding: A Multimodal Analysis of 'Flexing' in Instagram - Brahmana, Christanta Rejuna Phanes S; Ningrum, Dwi Kurnia Surya; Perangin-angin, Alemina Br. (Institut Agama Islam Negeri Palopo, 2023)
This study delves into the dynamic phenomenon of